Direct amorphous-to-cubic perovskite phase transformation for lead titanate - Leite, E. R.; Paris, E. C.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley, 2000)
The phase evolution of lead titanate processed by the polymeric precursor method was investigated by thermal analysis, X-ray diffraction, and high-resolution transmission electron microscopy. The results showed that the cubic perovskite PbTiO3 (PT) phase is formed from an inorganic amorphous precursor at a temperature of 444 °C. A gradual transition from cubic to tetragonal perovskite PT was observed with the increase of calcination time at this temperature. HRTEM results showed that the cubic PT particles have a size of around 5 nm. The identification of cubic PT as an intermediate phase supports the hypothesis that the chemical homogeneity was kept at the molecular level during the synthesis process, with no cation segregation.
Keywords: Amorphous materials; Calcination; Ceramic materials; Ferroelectric materials; High resolution electron microscopy; High temperature effects; Particle size analysis; Perovskite; Phase transitions; Thermoanalysis; Transmission electron microscopy; X ray crystallography; Lead titanate; Lead compounds